2021
DOI: 10.3389/fnins.2021.635483
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repurposing in the Treatment of Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is the most common cause of morbidity among trauma patients; however, an effective pharmacological treatment has not yet been approved. Individuals with TBI are at greater risk of developing neurological illnesses such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). The approval process for treatments can be accelerated by repurposing known drugs to treat the growing number of patients with TBI. This review focuses on the repurposing of N-acetyl cysteine (NAC), a drug cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 60 publications
0
8
0
1
Order By: Relevance
“…Parenthetically, phenserine demonstrates pharmacologically valuable AChE inhibition when administered to animals and humans, 38 , 43 45 in addition to useful non-cholinergically mediated actions. 26 , 46 However, it is AChE inhibition that likely also underpins phenserine’s dose-limiting actions. 44 In contrast, Posiphen lacks AChE inhibitory action and hence can be escalated to a higher dose in both humans and rodents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parenthetically, phenserine demonstrates pharmacologically valuable AChE inhibition when administered to animals and humans, 38 , 43 45 in addition to useful non-cholinergically mediated actions. 26 , 46 However, it is AChE inhibition that likely also underpins phenserine’s dose-limiting actions. 44 In contrast, Posiphen lacks AChE inhibitory action and hence can be escalated to a higher dose in both humans and rodents.…”
Section: Resultsmentioning
confidence: 99%
“… 6 Phenserine, initially developed as an oral, immediate release, AChE inhibitor that proved well tolerated in human studies (645 subjects for up to 1 year) and demonstrated an efficacy signal in AD, 27 29 , 45 , 48 has in recent studies demonstrated far more interesting pharmacological action by mitigating programmed neuronal cell death, synaptic loss, and neuroinflammation across multiple cellular and animal neuronal injury models at clinically translatable doses. 26 , 46 , 49 53 As a consequence and to optimize these more recent cholinergically and non-cholinergically mediated pharmacological actions, phenserine has re-entered clinical development as an extended controlled-release oral tablet formulation to maintain steady-state therapeutic drug levels and AChE inhibition in AD and traumatic brain injury human clinical trials. 54 In contrast, Posiphen was originally developed as a “cholinergically inert” APP synthesis inhibitor to lower Aβ generation and subsequent tau phosphorylation and associated neuroinflammation, 47 which have been confirmed by recent studies by others.…”
Section: Discussionmentioning
confidence: 99%
“…5). Pomimo dobrego wyrównania parametrów życiowych i elektrolitowych, niewystępowania cech infekcji, prowadzonego leczenia tywniejszych metod leczenia farmakologicznego TBI w fazie ostrej oraz redukujących ryzyko odległych powikłań, zwłaszcza u chorych z dominującymi zaburzeniami świadomości [25].…”
Section: Ryc 6 Kontrolny Obraz Tk Mózgu Przy Wypisie Ze Szpitala Prze...unclassified
“…These suggest the importance of antioxidant activation and immune response balance for recovery after brain injury. Indeed, both preclinical and clinical studies have found positive effects of NAC in several TBI models, including the weight drop model used here [ 5 , 6 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%